Analisis Tindak Tutur Ilokusi Percakapan pada Podcast Azizah Hanum dengan Tamu Undangan Maudy Ayunda: Kita Beragam, Kita Cantik - Muhammad Muslim Nasution; Dini Meidiyanti Putri; Julisah Izar (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
One of the phenomena contained in pragmatics which discusses the use of language in everyday, people's lives is illocutionarys peechacts. Illocutionary speech acts are known as The Act Of Doing Something or speech acts that are conveyed withth intention of an action. The purpose of this research is to find out the form and purpose of the speech acts contained in Azizah Hanum and Maudy Ayunda's podcast which discusses: kita beragam, kita cantik. This research will also later show which forms of speech mostly appear in the podcast. For the research method using a qualitative descriptive method that is describing the forms of speech found. The data collection technique was carried out by observing and noting techniques. Based onthe data analysis, four forms of speech were found with 26 data, namely assertive (12), directive (3), expressive (10), and commissive (1).